Low-Water Activity Foods: Increased Concern as Vehicles of Foodborne Pathogens - Beuchat, Larry R; Komitopoulou, Evangelia; Beckers, Harry; Betts, Roy P; Bourdichon, François; Joosten, Han M; Ter Kulie, Benno H (Journal of food protection, 2013)
Foods and food ingredients with low water activity (a(w)) have been implicated with increased frequency in recent years as vehicles for pathogens that have caused outbreaks of illnesses. Some of these foodborne pathogens can survive for several months, even years, in low-a(w) foods and in dry food processing and preparation environments. Foodborne pathogens in low-a(w) foods often exhibit an increased tolerance to heat and other treatments that are lethal to cells in high-a(w) environments. It is virtually impossible to eliminate these pathogens in many dry foods or dry food ingredients without impairing organoleptic quality. Control measures should therefore focus on preventing contamination, which is often a much greater challenge than designing efficient control measures for high-a(w) foods. The most efficient approaches to prevent contamination are based on hygienic design, zoning, and implementation of efficient cleaning and sanitation procedures in the food processing environment. Methodologies to improve the sensitivity and speed of assays to resuscitate desiccated cells of foodborne pathogens and to detect them when present in dry foods in very low numbers should be developed. The goal should be to advance our knowledge of the behavior of foodborne pathogens in low-a(w) foods and food ingredients, with the ultimate aim of developing and implementing interventions that will reduce foodborne illness associated with this food category. Presented here are some observations on survival and persistence of foodborne pathogens in low-a(w) foods, selected outbreaks of illnesses associated with consumption of these foods, and approaches to minimize safety risks.